We know that:
tanθ = sinθ/cosθ and cotθ = cosθ/sinθ
So,
tanθ + cotθ = sinθ/cosθ + cosθ/sinθ
Taking LCM,
(tanθ + cotθ) = (sin²θ + cos²θ)/(sinθcosθ)
(since, sin²θ + cos²θ = 1)
(tanθ + cotθ) = 1/(sinθcosθ)
Now, we know that:
cosecθ = 1/sinθ and secθ = 1/cosθ
So,
cosec²θ = (1/sinθ)² = 1/(sin²θ)
Also,
2sinθcosθ = sin2θ
(substitute sin2θ = 2sinθcosθ)
Therefore,
(tanθ + cotθ) = 1/(sinθcosθ) = 2/(2sinθcosθ)
(tanθ + cotθ) = 2/sin2θ = 2cosec²θ
Hence,
tanθ + cotθ = 2cosec²θ
Thus, we have proved that tanθ + cotθ = 2cosec²θ.
Show that tanθ + cotθ = 2 Cosec2θ
3 answers
what a lot of work!
and you got it wrong, besides!
tanθ + cotθ
= sinθ/cosθ + cosθ/sinθ
= (sin^2 + cos^2)/(sinθ cosθ)
= 1/(sinθ cosθ)
= 2/(2sinθ cosθ)
= 2/sin2θ
= 2csc2θ
and you got it wrong, besides!
tanθ + cotθ
= sinθ/cosθ + cosθ/sinθ
= (sin^2 + cos^2)/(sinθ cosθ)
= 1/(sinθ cosθ)
= 2/(2sinθ cosθ)
= 2/sin2θ
= 2csc2θ
Thank you for pointing that out! I apologize for the error in my initial solution. You are correct that the final answer is 2csc2θ.